In-Situ Annealing and Hydrogen Irradiation of Defect-Enhanced Germanium Quantum Dot Light Sources on Silicon - Lukas Spindlberger; Johannes Aberl; Antonio Polimeni; Jeffrey Schuster; Julian Hörschläger; Tia Truglas; Heiko Groiss; Friedrich Schäffler; Thomas Fromherz; Moritz Brehm (Crystals, 2020)
While light-emitting nanostructures composed of group-IV materials fulfil the mandatory compatibility with CMOS-fabrication methods, factors such as the structural stability of the nanostructures upon thermal annealing, and the ensuing photoluminescence (PL) emission properties, are of key relevance. In addition, the possibility of improving the PL efficiency by suitable post-growth treatments, such as hydrogen irradiation, is important too. We address these issues for self-assembled Ge quantum dots (QDs) that are co-implanted with Ge ions during their epitaxial growth. The presence of defects introduced by the impinging Ge ions results in pronounced PL-emission at telecom wavelengths up to room temperature (RT) and above. This approach allows us to overcome the severe limitations of light generation in the indirect-band-gap group-IV materials. By performing in-situ annealing, we demonstrate a high PL-stability of the defect-enhanced QD (DEQD) system against thermal treatment up to 600 °C for at least 2 h, even though the Ge QDs are structurally affected by Si/Ge intermixing via bulk diffusion. The latter, in turn, allows for emission tuning of the DEQDs over the entire telecom wavelength range from 1.3 µm to 1.55 µm. Two quenching mechanisms for light-emission are discussed; first, luminescence quenching at high PL recording temperatures, associated with the thermal escape of holes to the surrounding wetting layer; and second, annealing-induced PL-quenching at annealing temperatures >650 °C, which is associated with a migration of the defect complex out of the QD. We show that low-energy ex-situ proton irradiation into the Si matrix further improves the light emission properties of the DEQDs, whereas proton irradiation-related optically active G-centers do not affect the room temperature luminescence properties of DEQDs.